The Quality Assurance System for Higher Education in Norway - with Particular Reference to the Library Services - Salvesen, Helge (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2006)
Since the Pan-European Bologna Declaration of 1999, which introduced a qualitative improving programme for higher education in Europe, governments in many countries have initiated significant university reforms. In Norway the reforms were introduced fully in the academic year 2003-2004. This paper identifies the reforms and tries to relate them to the ideologies of new public management, globalization and efficiency.